Engines of Rebellion : Confederate Ironclads and Steam Engineering in the American Civil War - Bisbee, Saxon T., 1986- (Book collections on Project MUSE., 2018)
The development of steam propulsion machinery in warships during the nineteenth century, in conjunction with iron armor and shell guns, resulted in a technological revolution in the world's navies. Warships utilizing all of these technologies were built in France and Great Britain in the 1850s, but it was during the American Civil War that large numbers of ironclads powered solely by steam proved themselves to be quite capable warships. This book focuses on Confederate ironclads with American built machinery, offering a detailed look at marine steam-engineering practices in both northern and southern industry prior to and during the Civil War. It gives a contextual naval history of the Civil War, the creation of the ironclad program, and the advent of various technologies. The author analyzes the armored warships built by the Confederate States of America that represented a style adapted to scarce industrial resources and facilities.